Cultural Landscapes in the Asia-Pacific: Re-focusing UNESCO Designation on Community Participation - Dharmiasih, Wiwik (Forestry Faculty, Universitas Hasanuddin, 2020)
World Heritage Sites, designated by UNESCO, are a growing phenomenon in global governance. Sites are nominated for their Outstanding Universal Values with the objective of protecting against potential threats from man-made or natural causes. This article focuses on one type of recognition, the Cultural Landscape, which is unique because it is a living heritage site. Within Cultural Landscapes, people continue to carry out their lives and livelihoods as part of the site. The aim of this article is to examine the way community participation takes place in the designation of Cultural Landscapes. Findings highlight some ideas for researchers and policymakers to re-examine blind spots relative to community participation and offer some considerations for more meaningfully engaging local voices, particularly with respect to vulnerable populations and generational transition. Overall, research on Cultural Landscapes need not only examine what is being protected, but also must explore the new institutions being established, which can transform sites from within.